KETIDAKPASTIAN ITU MAHAL - Maman A. Djauhari (Fakultas Seni Rupa dan Desain ITB, 2007)
The uncertainty of life could be perceived as a blessing in disguise to those who are sane and sensible. The intellectual development of an individual determines the degree of such a perception. It is therefore necessary that we manage the uncertainty of life in such a way that we can achieve harmonious lives while making progress without the violation of the social norms. To do so, the humanities, are likely to be the relevant tools. The roles of these tools for managing the uncertainty of life are discussed in this article.